101 leadership actions for performance management - Malone, Ollie (HRD Pess, 2004)
Upgrade your leadership skills quickly and easily€"and produce results in your organization with a lot less effort. Each book in this collection focuses on a specific area of leadership and managerial effectiveness and offers 101 actions you can accomplish today to improve your impact. The books are easy-to-read and written by experts with real-world experience. Packed with involving activities that encourage thought and action, the books offer techniques that have been tried and proven effective in Fortune 500 companies. Read each title from cover to cover or one action-at-a-time. Either